Hydrogen direct reduction (H-DR) in steel industry—An overview of challenges and opportunities. (20th December 2021) - Wang, R.R.; Zhao, Y.Q.; Babich, A.; Senk, D.; Fan, X.Y.
Abstract: The steel industry is considered the most important basic industry and is crucial role for strengthening the national economy; however, its high energy intensity and carbon emissions render it a major contributor to global warming and climate change. To reduce the carbon footprint of the steel industry, and ultimately achieve the vision of carbon neutrality, countries and steel companies around the world are engaged in developing low-carbon steelmaking technologies. Hydrogen direct reduction (H-DR) technology, which uses 100% green H2 rather than conventional natural gas in the process, is currently considered the most promising technology. Thus, in this study, the feasibility of H-DR technology was discussed from the perspective of green hydrogen production and process adaptability. In the short term, the economic feasibility of H-DR is heavily dependent on the low-cost green hydrogen or high carbon emissions, the low efficiency of process and carbon-free product are problems that need to be solved, and H2 -rich shaft furnace direct reduction technology is considered a key transitional technology. In the long term, 80–90% of carbon emissions can be avoided on application of H-DR in the steel industry; therefore, the widespread application of H-DR technology is expected to be a milestone in the transition of the steel industry to cleaner production. Graphical abstract: Image 1 Highlights: Hydrogen direct reduction (H-DR) is the most promising ironmaking technology. The latest developments of H2 production and H-DR in steel industry are introduced. H-DR has a huge potential of reducing carbon emissions. Economic viability of H-DR mainly depends on low-cost green H2 or high carbon price.